PENGARUH KECERDASAN EMOSIONAL, KOMPETENSI DAN STRES KERJA TERHADAP KINERJA KARYAWAN RSUD BENGKULU TENGAH - Ilham Nopianto; Islamuddin Islamuddin; Meilaty Finthariasari (Yayasan Insani Mandiri Santani, 2020)
This study was to investigate the effect of emotional intelligence, competence and job stress on the performance of employees at Regional Public Hospital, Central Bengkulu. The aims of this study to determine the influence between emotional intelligence, competence and work stress on employee performance, both are partially and simultaneously. The object of this study was 149 employees of RSUD Central Bengkulu, with the convenience sampling method. Data collection methods are taken through questionnaires and observations. The results found the variables of emotional intelligence (X1), competence (X2), work stress (X3) partially, and simultaneously have a significant effect on employees’ performance variables (Y). This is seen from multiple linear regression equation where Y=1,690+0.390 (X1)+0.170 (X2)-0.248 (X3). While, the multiple linear regression analysis showed its influence on emotional intelligence variables, competence and work stress on employee performance (Y), which is shown from the adjusted R square value was 0.812. This means that the magnitude of influence of variable emotional intelligence, competence and work stress is only able to influence 81.2% on employee performance variable (Y).